A Longitudinal Analysis of Legitimizing Sustainability: Executive and Institutional Discourse as Strategic Communication - Yalcinyigit, Serap; Akbas, Halil Emre (WILEY, 2026)
This study explores sustainability discourses from legitimacy theory and strategic communication perspectives. For this purpose, a longitudinal corpus was constructed from Carbon Disclosure Project (CDP) T & uuml;rkiye reports published between 2010 and 2024, covering the discourses of global, governmental, sponsor, and executive actors. Using a dictionary-based computational text analysis combined with qualitative thematic interpretation, approximately 57,000 words were analyzed to identify temporal changes, thematic patterns, and actor-specific discursive strategies. Results show that the discourses were linguistically stable, but the themes changed over time with increasing use of policy-driven and risk-aware language. Moreover, the analysis indicated clear discursive distinctions, global forewords emphasizing governance and risk narratives for investors while local texts framed more towards policy compliance and strategic opportunities. These patterns reveal that sustainability discourses function as strategic communication through which different actors negotiate legitimacy with stakeholders over time, particularly in a developing economy context.
Keywords: corporate sustainability; discourse; legitimacy; strategic communication; sustainability reporting; CORPORATE SOCIAL-RESPONSIBILITY; ORGANIZATIONS; OPPORTUNITIES; DISCLOSURE; RISKS; TEXT; CSR; Business & Economics; Environmental Sciences & Ecology